Risk of hospitalization associated with body mass index and weight changes among prevalent haemodialysis patients - Carrero, Juan J; Cabezas-Rodríguez, Ivan; Qureshi, Abdul R; Floege, Jürgen; Ketteler, Markus; London, Gerard; Locatelli, Francesco; Memmos, Dimitrios; Goldsmith, David; Ferreira, Aníbal; Nagy, Judit; Teplan, Vladimir; et al. (Nefrología, 2018)
The impact of body mass index (BMI) and body weight on hospitalization rates in haemodialysis patients is unknown. This study hypothesizes that being either underweight or obese is associated with a higher hospitalization rate. Observational study of 6296 European haemodialysis patients with prospective data collection and follow-up every six months for three years (COSMOS study). The risk of being hospitalized was estimated by a time-dependent Cox regression model and the annual risk (incidence rate ratios, IRR) by Poisson regression. We considered weight loss, weight gain and stable weight. Weight change analyses were also performed after patient stratification according to their baseline BMI. A total of 3096 patients were hospitalized at least once with 9731 hospitalizations in total. The hospitalization incidence (fully adjusted IRR 1.28, 95% CI [1.18-1.39]) was higher among underweight patients (BMI <20kg/m2) than patients of normal weight (BMI 20-25kg/m2), while the incidence of overweight (0.88 [0.83-0.93]) and obese patients (≥30kg/m2, 0.85 [0.79-0.92]) was lower. Weight gain was associated with a reduced risk of hospitalization. Conversely, weight loss was associated with a higher hospitalization rate, particularly in underweight patients (IRR 2.85 [2.33-3.47]). Underweight haemodialysis patients were at increased risk of hospitalization, while overweight and obese patients were less likely to be hospitalized. Short-term weight loss in underweight individuals was associated with a strikingly high hospitalization rate.
Keywords: hodnocení rizik; Male; Risk Assessment; Obesity; hubenost; hospitalizace; dialýza ledvin; obezita; Aged; Prospective Studies; mužské pohlaví; senioři; Body Weight; Thinness; Renal Dialysis; lidé; ženské pohlaví; Humans; Body Mass Index; Hospitalization; index tělesné hmotnosti; Female; lidé středního věku; tělesná hmotnost; Middle Aged; prospektivní studie